Assessment of clinical, biochemical, and radiological outcomes following intra-articular injection of Wharton jelly-derived mesenchymal stromal cells in patients with knee osteoarthritis: A prospective clinical study. Issue 37 (16th September 2022) - Günay, Ali Eray; Karaman, Ibrahim; Guney, Ahmet; Karaman, Zehra Filiz; Demirpolat, Eren; Gonen, Zeynep Burcin; Dogan, Serap; Yerer, Mukerrem Betul
Abstract : The aim of the present study was to perform clinical, biochemical, and radiological evaluation of the efficacy of mesenchymal stem cells derived from Wharton jelly (WJ) present within the human umbilical cord in the treatment of knee osteoarthritis. Between 2018 and 2019, 10 patients with knee osteoarthritis for whom the conservative treatment was not beneficial were included in the study. Patients were clinically, radiologically, and biochemically evaluated before treatment initiation. Thereafter, the patients were intra-articularly injected using a solution containing 1 × 10 8 WJ-derived MSCs. Evaluations were performed on day 21 (V1) and 42 (V2) and month 3 (V3), 6 (V4), and 12 (V5) after the procedure. At 1-year post-injection, visual analogue scale, Western Ontario and McMaster Universities Osteoarthritis Index, and Lequesne scores of patients were lower than those observed during the initial evaluation, whereas the mean 36-Item Short Form Health Survey score was higher. Cartilage thicknesses were found to be increased in all regions except in the medial femur, medial posterior femur, lateral posterior femur, and lateral posterior tibia regions in magnetic resonance imaging. A significant increase was observed in tumor necrosis factor-alpha, interleukin-1β, adiponectin, resistin, and interleukin-6 levels compared with pre-injection values. The leptin levels at 6-month and 1-year controls were lower than the pre-injection levels, and the decrease observed at 6 months was significant. In patients with knee osteoarthritis, intra-articular WJ-derived MSC injection causes significant pain reduction, satisfactory functional improvement, and increased patient satisfaction following a 1-year follow-up. These clinical improvements were supported by magnetic resonance images, along with changes in adiponectin and leptin levels in synovial fluid. Level of evidence: IV.